Preferences of Policy Actors in Implementing Family Hope Programs in The City of Makassar - Mita Arnika; Alwi; Nurdin Nara (Institute of Computer Science (IOCS), 2021)
The implementation of the Family of Hope Program in the city of Makassar encourages cooperation between agencies in each region to realize the goals of the vision and mission of unity in overcoming poverty in the city of Makassar. policy actors, it must be ensured that the implementation of policies is effective and efficient, and they can understand or develop their knowledge with extraordinary skills. This research is carried out by in-depth interviews, documentation and observation. Data reduction techniques to analyze data and Draw data conclusions, focus actor preference is an option to develop actor knowledge that is able to motivate the community directly with poor families, it is hoped that the knowledge possessed by actors can affect the poor, so that it can get out of line poverty, by using the ability to have, as well as the implementation of government policies As set out in the guidelines as mandatory obligations, such as attending family capacity building meetings by studying learning modules such as childcare education, becoming more parents, and managing finances with the implementation of these tasks actors there are two keys to success in the preferences of policy actors such as improving good (competent) performance, succeeding in increasing the motivation of beneficiary families (KPM) so that they avoid the poverty line.